2010
DOI: 10.1111/j.1524-4741.2009.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

True Recurrences and New Primary Tumors Have Different Clinical Features in Invasive Breast Cancer Patients with Ipsilateral Breast Tumor Relapse After Breast-Conserving Treatment

Abstract: Ipsilateral breast tumor relapse (IBTR) after breast-conserving treatment (BCT) may represent two distinct types of lesion, including a true recurrence (TR) or a new primary tumor (NPT). The aim of this study was to ascertain the difference between TRs and NPTs and to show the clinical significance of classifying IBTR into these two types of recurrence. Patients (n = 2,075) with unilateral invasive breast cancer who underwent BCT between 1987 and 2005 at Saitama Cancer Center were analyzed. IBTR was classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
(62 reference statements)
0
18
0
2
Order By: Relevance
“…TR and NPT have different natural histories, prognosis, and in turn different implications for therapeutic management [1, 2, 3, 4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TR and NPT have different natural histories, prognosis, and in turn different implications for therapeutic management [1, 2, 3, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…However, as each case has different clinical relevance (evolution, prognosis and therapeutic management), it is necessary to distinguish in these patients between a true local recurrence (TR) of a previous tumor, and the appearance of a new primary tumor (NPT) [1, 2, 3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Les deux facteurs le plus souvent pris en compte sont la localisation de la récidive par rapport à la première tumeur et le type histologique (c'est-à-dire canalaire, lobulaire, tubuleux… mais non in situ versus invasif) [37,48,58,71,89,110]. La différence entre vraie récidive et nouveau cancer repose actuellement sur des critères mal défi nis, non standardisés.…”
Section: Dossierunclassified
“…Les nouveaux cancers auraient pour la plupart des auteurs une survie (survie globale, survie spécifi que et survie sans métastase) meilleure que les « vraies RL » [48,58,71,110]. Dans l'étude de Huang et al [48], le risque de deuxième RL serait plus important pour les nouveaux cancers que pour les vraies RL, mais la prise en charge locale était signifi cativement diffé-rente : 94 % de MT en cas de nouveau cancer, 75 % en cas de vraie RL, avec 15 % de patientes sans traitement local lors de la RL.…”
Section: Dossierunclassified
“…Several studies have attempted to classify the two distinct types of IBTR by using tumor location, histological subtype, surgical margin status of the primary tumor, estrogen receptor status and human epidermal growth factor receptor 2 (HER2) status. These studies demonstrated that patients with NP had significantly better survival rates than patients with TR . Although the importance of classifying IBTR is well known, IBTR is difficult to classify, especially the IBTR that occurs near the primary lumpectomy scar.…”
mentioning
confidence: 99%